PERFORMANCE OF THE PHYSIOTHERAPIST IN THE TREATMENT OF CHILDREN WITH THE DIAGNOSIS OF HYDROCEPHALUS: ACTION IN THE CHILD’S NEUROPSYCOMOTOR DEVELOPMENT - Da Silva Araújo, Cíntia; Nayelle Ferreira De Sousa , Sara; Silva de Oliveira, Elen; Maia Souza, Clevane; Oliveira Dantas, Shirlei; Sacramento Santana, Uilma; Luísa Sousa Braga, Maria; Dos Santos Moreira, Fernanda; Carvalho Andrade, Maycon; Silva Bena, Alanildes; Cavalcante Costa, Luciana; Beatriz Cavalcanti Da Costa, Letícia; et al. (Health and Society, 2023)
This article aims to describe the physiotherapeutic techniques applied in the intervention of the disease, to raise socioeconomic aspects of the relatives of children with hydrocephalus, and to classify the profile and lifestyle of these children after contact with the physiotherapist. Therefore, the methodology is a qualitative research, based on bibliographic surveys contained in databases. It is concluded that physiotherapy does not act in the treatment of the disease itself, but in the sensory and motor dysfunctions that the disease causes, and from this, the physiotherapy applications for the habilitation or rehabilitation of the functions interrupted by hydrocephalus can be in different ways, depending on the degree of evolution of damage caused by hydrocephalus. Thus, the earlier the diagnosis is made and the physiotherapeutic treatments are started, the greater the gain in motor function and functional independence. It is also worth mentioning that the family’s participation and their economic conditions can directly influence the child’s development and recovery.